2001
DOI: 10.1177/194589240101500610
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Application of the α2-Adrenoceptor Agonist BHT-920 Produces Decongestion in the Cat

Abstract: The effect of alpha2-selective adrenoreceptor activation on nasal cavity dimension in an experimental model of congestion has not been defined. Presently, we used acoustic rhinometry to evaluate the decongestant activity of BHT-920, a selective alpha2-adrenergic agonist against nasal congestion produced by intranasal compound 48/80. Administration of the mast cell liberator compound 48/80 (1%) into a nasal passageway decreased ipsilateral volume and minimum cross-sectional area by 73 +/- 4% and 42 +/- 6%, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Oral administrations of compound A in the in vivo rat preparation did not cause increase in blood pressure up to 30 mg/kg (with a plasma concentration of 19 M), whereas phenylephrine produced significant hypertensive effects (24 and 53 mm Hg with plasma concentrations of 0.3 and 0.7 M at 10 and 20 mg/kg, respectively). Phenylephrine (␣ 1 -adrenoceptor agonist) and the standard decongestants, phenylpropanolamine, pseudoephedrine, and oxymetazoline (mixed ␣ 1 -and ␣ 2 -adrenoceptor agonists) also caused pronounced increase in blood pressure at doses that attenuated nasal congestion in the cat congestion model McLeod et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Oral administrations of compound A in the in vivo rat preparation did not cause increase in blood pressure up to 30 mg/kg (with a plasma concentration of 19 M), whereas phenylephrine produced significant hypertensive effects (24 and 53 mm Hg with plasma concentrations of 0.3 and 0.7 M at 10 and 20 mg/kg, respectively). Phenylephrine (␣ 1 -adrenoceptor agonist) and the standard decongestants, phenylpropanolamine, pseudoephedrine, and oxymetazoline (mixed ␣ 1 -and ␣ 2 -adrenoceptor agonists) also caused pronounced increase in blood pressure at doses that attenuated nasal congestion in the cat congestion model McLeod et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…They also have considerable activity in blood vessels of the nasal mucosa, where their activity can predominate over ␣ 1 -adrenoceptors (Andersson and Bende, 1984;Lacroix and Lundberg, 1989;Wang and Lung, 2003). Indeed, activation of ␣ 2 -adrenoceptors may be the preferred choice for causing nasal vasoconstriction and nasal decongestion (McLeod et al, 2001). The present experiments were therefore performed to evaluate the activity of phenylpropanolamine at vascular ␣ 1 -and ␣ 2 -adrenoceptors.…”
mentioning
confidence: 99%
“…However, these receptors are distinct from the rat I 2 -receptor to which SCH 79687 binds. We have previously demonstrated that activation of ␣ 2 -adrenergic receptors with drugs such as BHT-920 produced nasal decongestion in the cat (McLeod et al, 2001b). However, the observation that SCH 79687 did not alter the inhibitory actions of clonidine on EFS-induced HSV contractions or affect baseline HSV tone suggest that ␣ 2-adrenoceptors are not activated in vitro at the concentration presently studied.…”
Section: Discussionmentioning
confidence: 49%
“…Peripheral H 3 receptors may serve as a target for the development of novel antiallergy drugs, in particular, mechanism-based decongestants (McLeod et al, 1999(McLeod et al, , 2001b. These receptors prejunctionally modulate sympathetic neurotransmission and attenuate a variety of organ responses governed by sympathetic nervous system regulation (Koss and Hey, 1992;McLeod et al, 1993;Yu et al, 2001).…”
mentioning
confidence: 99%